Pelatihan Google Classroom Sebagai Media Pembelajaran Daring di SMP Al-Hamidiyah Palembang - Rosyidah, Masayu; Winda, Meilyana; Karnadi, Karnadi (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2021)
The impact of the Covid-19 pandemic is almost evenly distributed in all sectors of life, including education. The existence of the Ministry of Education and Culture's policy forces all teachers to be able to present distance learning. The problem with partners is that they haven't used the Google Classroom application optimally. The method given in this community service activity is socialization and direct training / practice by the teacher who is accompanied by a community service team. The results obtained from 20 respondents were 90% familiar with the material presented, as many as 85% were able to apply it in the class later, and the rest gave other responses.